A novel mechanism of tandem activation of ryanodine receptors by cytosolic and SR luminal Ca2+ during excitation–contraction coupling in atrial myocytes. (1st February 2017) - Maxwell, Joshua T.; Blatter, Lothar A.
Abstract : Key points: In atrial myocytes excitation–contraction coupling is strikingly different from ventricle because atrial myocytes lack a transverse tubule membrane system: Ca 2+ release starts in the cell periphery and propagates towards the cell centre by Ca 2+ ‐induced Ca 2+ release from the sarcoplasmic reticulum (SR) Ca 2+ store. The cytosolic Ca 2+ sensitivity of the ryanodine receptor (RyRs) Ca 2+ release channel is low and it is unclear how Ca 2+ release can be activated in the interior of atrial cells. Simultaneous confocal imaging of cytosolic and intra‐SR calcium revealed a transient elevation of store Ca 2+ that we termed 'Ca 2+ sensitization signal'. We propose a novel paradigm of atrial ECC that is based on tandem activation of the RyRs by cytosolic and luminal Ca 2+ through a 'fire–diffuse–uptake–fire' (or FDUF) mechanism: Ca 2+ uptake by SR Ca 2+ pumps at the propagation front elevates Ca 2+ inside the SR locally, leading to luminal RyR sensitization and lowering of the cytosolic Ca 2+ activation threshold. Abstract: In atrial myocytes Ca 2+ release during excitation–contraction coupling (ECC) is strikingly different from ventricular myocytes. In many species atrial myocytes lack a transverse tubule system, dividing the sarcoplasmic reticulum (SR) Ca 2+ store into the peripheral subsarcolemmnal junctional (j‐SR) and the much more abundant central non‐junctional (nj‐SR) SR. Action potential (AP)‐induced Ca 2+ entry activates Ca 2+ ‐induced Ca 2+ release (CICR) from j‐SR ryanodine receptor (RyR) Ca 2+ release channels. Peripheral elevation of [Ca 2+ ]i initiates CICR from nj‐SR and sustains propagation of CICR to the cell centre. Simultaneous confocal measurements of cytosolic ([Ca 2+ ]i ; with the fluorescent Ca 2+ indicator rhod‐2) and intra‐SR ([Ca 2+ ]SR ; fluo‐5N) Ca 2+ in rabbit atrial myocytes revealed that Ca 2+ release from j‐SR resulted in a cytosolic Ca 2+ transient of higher amplitude compared to release from nj‐SR; however, the degree of depletion of j‐SR [Ca 2+ ]SR was smaller than nj‐SR [Ca 2+ ]SR . Similarly, Ca 2+ signals from individual release sites of the j‐SR showed a larger cytosolic amplitude (Ca 2+ sparks) but smaller depletion (Ca 2+ blinks) than release from nj‐SR. During AP‐induced Ca 2+ release the rise of [Ca 2+ ]i detected at individual release sites of the nj‐SR preceded the depletion of [Ca 2+ ]SR, and during this latency period a transient elevation of [Ca 2+ ]SR occurred. We propose that Ca 2+ release from nj‐SR is activated by cytosolic and luminal Ca 2+ (tandem RyR activation) via a novel 'fire—diffuse–uptake–fire' (FDUF) mechanism. This novel paradigm of atrial ECC predicts that Ca 2+ uptake by sarco‐endoplasmic reticulum Ca 2+ ‐ATPase (SERCA) at the propagation front elevates local [Ca 2+ ]SR, leading to luminal RyR sensitization and lowering of the activation threshold for cytosolic CICR. Key points: In atrial myocytes excitation–contraction coupling is strikingly different from ventricle because atrial myocytes lack a transverse tubule membrane system: Ca 2+ release starts in the cell periphery and propagates towards the cell centre by Ca 2+ ‐induced Ca 2+ release from the sarcoplasmic reticulum (SR) Ca 2+ store. The cytosolic Ca 2+ sensitivity of the ryanodine receptor (RyRs) Ca 2+ release channel is low and it is unclear how Ca 2+ release can be activated in the interior of atrial cells. Simultaneous confocal imaging of cytosolic and intra‐SR calcium revealed a transient elevation of store Ca 2+ that we termed 'Ca 2+ sensitization signal'. We propose a novel paradigm of atrial ECC that is based on tandem activation of the RyRs by cytosolic and luminal Ca 2+ through a 'fire–diffuse–uptake–fire' (or FDUF) mechanism: Ca 2+ uptake by SR Ca 2+ pumps at the propagation front elevates Ca 2+ inside the SR locally, leading to luminal RyR sensitization and lowering of the cytosolic Ca 2+ activation threshold.